Новые исследования в Жаботине - Дараган, М.Н.; Подобед, В.А. (Археологія і давня історія України, 2019)
Работа посвящена публикации результатов
раскопок на эталонном памятнике начала раннего железного века Днепровской правобережной
Лесостепи — поселении у с. Жаботин. Описаны
вновь выявленные объекты (ров, пересекающий центральную площадку поселения, хозяйственные ямы
и завал глиняной обожженной обмазки), проанализирована стратиграфия и дан детальный анализ
находок из закрытых археологических комплексов. Новые исследования не только подтвердили периодизационную колонку поселения, но и позволили продлить ее до начала V в. до н. э. The focus of the work is the publication of the results
of the excavations on the reference monument at the beginning of the early Iron Age of the Dnieper
Right Bank Forest-Steppe — the settlement near the village of Zhabotin. The article includes the description
of newly discovered objects (ditch, pits), analysis of stratigraphy and a detailed analysis of finds from
closed archaeological complexes. For understanding the spatial structure of the settlement, a very important
discovery was Site 23, a ditch that crossed the inhabited area of the plateau of the settlement from West to East.
The ditch passes, apparently, through the whole of the central part of the monument, dividing it into two
parts. The ditch was built in the initial phase of the settlement. It should be noted that during the period of
the ditch’s functioning, the separated parts of the settlement were inhabited in the area of the ditch.
The complexes were investigated both prior to it (pit 1) with materials from the Zhabotin 1 horizon (first
half of the 8th BCE) and constructed after his backfill (pit 2, of the second half of the 7th BCE). It is noteworthy
that in pit 2 a fragment of South Ionian bowl, most likely from Miletos, was found. It must be type
Schlotzhauer 6 (subtype 6.2.B to 6.5), most likely to be dated between 660/50—630/20 BCE. At excavation
Site 24, a pits from the 8th — first half of the 7th BCE and the second half of the 6th beginning of the 5th BCE
was investigated. Studies of material complex from the ditch and different pits not only confirmed the periodization
frame of the settlement to 8—7 century BC, but also allowed that it extended until the beginning of the
5th BCE. Based on the new materials, the chronological frames of Zhabotin and Motroninsky hillforts (located
at the distance of 4.5 km), can be linked suggesting that they partially overlap each other.